L’accouchement par césarienne en Turquie : décision médicale ou tendance imposée ? - Selen Göbelez (Anthropologie & Santé)
The cesarean section delivery rate in Turkey is currently the highest among OECD member countries, and has increased from 21% in 2002 to 62,8 % in 2022. Despite the introduction of the “Caesarean section law” in 2012, this rate has not declined. Drawing on qualitative research, this article analyzes the factors underlying this trend, taking into account the perspectives of healthcare professional and mothers, as well as political measures taken by health authorities to reduce this rate. The issue of women’s choices of delivery methods is intertwined with the multidimensional network of social and political relations, including public debates, socio-cultural representations of childbirth, the healthcare system, the heavy workload of professionals and the search for organisational comfort and risk avoidance.